Social networking usage and mental health problems in the Kurdistan region of Iraq during the COVID-19 outbreak and lockdown - Dyari S. Hama amin; Parzheen J. Mohammad (Discover Psychology, 2024)
Abstract The COVID-19 outbreak, as an international health emergency, led to uncertainty. Pandemics can be stressful and anxiety-producing for community individuals. Moreover, due to lockdown measures implemented to slow down the spread of the disease, an increase in the usage of social media was reported. Therefore, this study aims to find the prevalence of mental health problems and the level of social media usage during the outbreak of COVID-19 in the Kurdistan region, Iraq. Furthermore, the relationship between mental health problems (i.e., depression, anxiety, and stress) and social media usage is explored. The study was cross-sectional; the data was collected through a snowball sampling method in which 355 participants completed an online questionnaire. Social networking usage questionnaire, Hopkins Symptom Checklist-15 (HSCL-25), and Perceived Stress Scale (PSS) were used as measurement tools. The results showed that the level of social networking usage was moderate. As for mental health problems, 76.5% of the respondents showed moderate to high stress levels, 56.4% reported experiencing depression, and 37.4% reported experiencing anxiety. Significant gender differences were found in depression, anxiety, and stress, with females scoring higher in all categories. In the mental health problem domains, only depression scores positively correlated with social media usage. The findings also showed social networking usage is associated with higher depression and anxiety; however, the effect sizes were small. Therefore, more research into this matter is necessary in the cultural context of the Kurdistan region to reach conclusive results.